A high-performance brushless permanent-magnet motor for domestic appliances - Lee, Hong Rui (Nanyang Technological University, 2024)
This paper presents the design and performance evaluation of a high-performance brushless permanent-magnet (BLPM) motor specifically tailored for domestic appliances. With the increasing demand for energy-efficient and reliable solutions in the household appliance industry, the development of compact and efficient electric motors is essential. BLPM motors offer significant advantages such as high efficiency, compact size, and low maintenance requirements, making them ideal candidates for various household applications. However, further advancements are needed to optimize their performance and maximize energy savings in domestic appliances. The proposed motor design integrates advanced permanent magnet technology with brushless operation to achieve superior performance characteristics, including high efficiency, enhanced torque density, and reduced maintenance requirements. This paper will explore key factors influencing BLPM motor efficiency, including design considerations and different configurations. Performance evaluation of the motor is conducted through the program JMAG. Key performance metrics including efficiency and torque-speed characteristics are measured and analyzed to validate the effectiveness of the proposed design. Overall, the presented brushless permanent-magnet motor offers a compelling solution for enhancing the energy efficiency and reliability of domestic appliances. Its high performance, compact design, and compatibility with advanced control systems position it as a promising technology for meeting the evolving demands of the household appliance industry in the quest for sustainable and eco-friendly solutions.